2023
DOI: 10.1002/14651858.cd008165.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve the appropriate use of polypharmacy for older people

Judith A Cole,
Daniela C Gonçalves-Bradley,
Mubarak Alqahtani
et al.

Abstract: Interventions to improve the appropriate use of polypharmacy for older people. Cochrane database of systematic reviews (Online),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 145 publications
0
17
0
Order By: Relevance
“…2 13–15 80 87–90 Reviews covering over 150 primary studies reported no differences in all-cause mortality and no clear evidence of benefit in reduced hospitalisations, when comparing interventions to usual care. 13 80 88 91–94 There were also no differences in quality of life, adverse drug reactions, readmission rates, primary care visits and emergency department visits. 13 80 92–94 Two reviews have highlighted some economic benefits in reducing healthcare expenditure, but others highlight inconsistencies due to low-quality evidence.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…2 13–15 80 87–90 Reviews covering over 150 primary studies reported no differences in all-cause mortality and no clear evidence of benefit in reduced hospitalisations, when comparing interventions to usual care. 13 80 88 91–94 There were also no differences in quality of life, adverse drug reactions, readmission rates, primary care visits and emergency department visits. 13 80 92–94 Two reviews have highlighted some economic benefits in reducing healthcare expenditure, but others highlight inconsistencies due to low-quality evidence.…”
Section: Resultsmentioning
confidence: 87%
“…One common approach uses simple cut offs of age (commonly ≥65 years) combined with cut offs of medications (frequently ≥5) and this was the main inclusion criterion for the majority of trials. 13 Another approach adopted by multiple national recommendations advocate case finding through high-risk groups. 36–38 For instance, both NICE guidelines and the Australian Commission on Safety and Quality in Healthcare recommend greater attention for older people with frailty, and complex multimorbidity and co-existing mental and physical health problems.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations